Saudi Aramco: Circular Economy and Sustainability in the Oil and Gas Industry - Eltayeb, Ahmed Y. (International Journal of Supply Chain Management, 2025)
This paper explores Saudi Aramco's commitment to sustainability and circular economy principles, highlighting key initiatives that enhance environmental performance and local content development [1]. Utilizing an integrated approach, the paper examines how Aramco implements strategies related to climate change, resource efficiency, and community engagement. The findings illustrate the company's significant contributions to job creation, GDP growth, and supply chain resilience. The paper argues that Aramco's efforts can serve as a model for other sectors aiming to achieve sustainable practices.